2018
DOI: 10.1097/sap.0000000000001561
|View full text |Cite
|
Sign up to set email alerts
|

Does Bowstringing Affect Hand Function in Patients Treated With A1 Pulley Release for Trigger Fingers?

Abstract: We aimed to inspect bowstringing after percutaneous and open release of the A1 pulley for trigger digits and its influence on hand function. Sixty-two patients with a resistant trigger digit were randomized to undergo either open release or percutaneous release of the A1 pulley. We quantified bowstringing of the digit using ultrasonography preoperatively and at 12 and 24 weeks after surgery. Pain on a visual analog scale; Disabilities of the Arm, Shoulder, and Hand questionnaire; pinch power; and grip strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…While all digits that underwent open release had complete resolution of symptoms, 3% of the digits that underwent USGAR had persistent triggering which resolved after repeat USGAR. There were no major or minor complications reported in this study 21 …”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…While all digits that underwent open release had complete resolution of symptoms, 3% of the digits that underwent USGAR had persistent triggering which resolved after repeat USGAR. There were no major or minor complications reported in this study 21 …”
Section: Discussionmentioning
confidence: 52%
“…Two studies did not specify which digits were treated 11,19 . Three studies excluded the treatment of the thumb 12,13,21 . Case numbers ranged from 15 to 104 procedures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experience, Pseudo-Dupuytren tissue of the palmar aponeurosis present at time of open trigger nger release may be worsened by surgery in the already transformed aponeurosis. Recently published biomechanical studies found possible bow stringing phenomenon of exor tendons after pulley release which may be another factor contributing to postoperative discomfort 8,9 .…”
Section: Introductionmentioning
confidence: 99%